A molecular dynamics approach to nanostructuring of particles produced via aerosol cationic photopolymerization. (23rd February 2019) - Bazzano, Marco; Marchisio, Daniele; Sangermano, Marco; Wörner, Michael; Pisano, Roberto
Graphical abstract: Highlights: Description of transport phenomena in aerosol droplets via molecular simulations. Mechanistic understanding of the link between formulation and particle structuring. Design of formulations which produce particles with different structural properties. Control of nano-structuring of micro-particles via molecular simulations. Abstract: Structuring of particles obtained by aerosol photopolymerization is here described from both the experimental and the simulation point of view. Transport phenomena occurring within aerosol droplets are studied in order to identify the key issues that must be carefully designed when considering particles structuring. In particular, phase separation and diffusion of the reacting species were evaluated using molecular dynamics simulations, allowing the identification of a series of formulation parameters such as the composition of a mixed solvent (hexadecane and 2-octanone) or the addition of a chain transfer reagent, which are crucial for the control of phase separation and, thus, of the final morphology of the microparticles. The results were compared with morphology analyses obtained from the experimental work. We also found that molecular simulations were useful for the decoupling of the effects of different solvents which were thus treated separately. The interplay between phase separation and gelation rates was also found to be crucial in the structuring process. For example, the ratio between hexadecane and a chain transfer reagent seemed to strongly affect the final morphology of micro-particles.